Quality evaluation of frying oil deterioration by dielectric spectroscopy. (July 2016) - Yang, J.; Zhao, K.S.; He, Y.J.
Abstract: Dielectric measurements were carried out on the soybean oil that already used for frying dough of different moisture or heating the oil without dough (blank oil) over a frequency range of 40 Hz–100 MHz to evaluate the deterioration of the oil with frying time. A distinct dielectric relaxation caused by the dipole orientation polarization was observed at about 10 MHz. Dielectric parameters characterizing the relaxation feature were obtained by fitting Cole–Cole equation to the dielectric data. The relaxation time stayed around at 10 −8  s with frying time, indicating that the size of the polar components have no change during the frying. Dielectric increment and dielectric loss increased linearly with frying time and the moisture contents of the dough, which was in agreement with the density of oil (measured in a separate experiment) that is in proportion to the deterioration. The time dependence of conductivity was different for the blank oil and that of oil used to fry dough, leading to the conclusion that the conductivity was mainly affected by the volatile decomposition products. The results show that dielectric spectroscopy could be a useful tool to evaluate frying oil. Highlights: The relationship between oil deterioration and the dielectric properties of oil was studied. The oil deterioration degree was evaluated accurately, and decomposition of specific noxious products was monitored. A promising tool to evaluate the quality of frying oil was provided.